2023
DOI: 10.1111/jcmm.17933
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory role of bone marrow mesenchymal stem cells‐derived exosome in non‐small‐cell lung cancer: microRNA‐30b‐5p, EZH2 and PI3K/AKT pathway

Tong Wu,
Qi Tian,
Ruiji Liu
et al.

Abstract: Exosomal microRNA (miRNA) exerts potential roles in non‐small‐cell lung cancer (NSCLC). The current study elucidated the role of miR‐30b‐5p shuttled by bone marrow mesenchymal stem cells (BMSCs)‐derived exosomes in treating NSCLC. Bioinformatics analysis was performed with NSCLC‐related miRNA microarray GSE169587 and mRNA data GSE74706 obtained for collection of the differentially expressed miRNAs and mRNAs. The relationship between miR‐30b‐5p and EZH2 was predicted and confirmed. Exosomes were isolated from B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Since the impact of oxidative stress on FA has been already well discussed [28,[40][41][42], the findings reported here might be helpful for the experimental management of FA. MiR-30b-5p in this pathway may act as a tumor suppressor, repressing cell proliferation and the cell cycle [43][44][45]. It is also associated with breast cancer and NSCLC [45,46].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the impact of oxidative stress on FA has been already well discussed [28,[40][41][42], the findings reported here might be helpful for the experimental management of FA. MiR-30b-5p in this pathway may act as a tumor suppressor, repressing cell proliferation and the cell cycle [43][44][45]. It is also associated with breast cancer and NSCLC [45,46].…”
Section: Resultsmentioning
confidence: 99%
“…MiR-30b-5p in this pathway may act as a tumor suppressor, repressing cell proliferation and the cell cycle [43][44][45]. It is also associated with breast cancer and NSCLC [45,46]. MiR-1246 can influence the stemness and resistance of cancer cells to therapeutics and appears to have a role in NSCLC [21,47].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have demonstrated that miRNAs encapsulated in native EVs derived from MSCs, such as miR-7-5p, miR-146b, miR-142-3p, and miR-let-7c, are capable of suppressing the development and metastasis of cancer. 16–18 For example, a recent study 19 by Wang et al elucidated that miR-30b-5p shuttled by bone marrow MSC-derived exosomes could promote cell apoptosis and prevent tumorigenesis in non-small cell lung cancer (NSCLC) via the EZH2/PI3K/AKT axis. Conversely, a number of studies indicated the tumor-promoting effect of MSC-derived EVs, 20–23 likely due to the enriched presence of tumor-supportive miRNAs ( e.g.…”
Section: Extracellular Vesicles For Cancer Therapymentioning
confidence: 99%
“…Exocrine miR-30b-5p from bone marrow mesenchymal stem cells plays a tumor inhibitory role in NSCLC by inhibiting EZH2 and PI3K/AKT pathways. The results suggest that exocrine from bone marrow mesenchymal stem cells may be used as a new therapeutic strategy for NSCLC ( 81 ). Similarly, miR-514b-5p promotes the progress of NSCLC by targeting SGTB through PI 3-K/AKT and p38 signal pathways.…”
Section: Microrna Affects Lung Cancer Development Through the Pi3k/ak...mentioning
confidence: 99%